Neoichnology of a Lake Margin in the Canadian Aspen Parkland Region, Cooking Lake, Alberta - Ryusuke Kimitsuki; John-Paul Zonneveld; Baptiste Coutret; Kelly Rozanitis; Yuhao Li; Kurt Konhauser; Murray K. Gingras (Sedimentologika)
Neoichnology provides insights essential for interpreting trace fossils in the rock record. Despite the wealth of studies conducted in marine nearshore environments, non-marine environments including lacustrine settings have received comparably little attention. Moreover, previous neoichnological studies of lakes are restricted to arid, semi-arid, tropical, and alkaline lakes, and there is a gap in knowledge of lakes in higher latitudes. The lake biome is controlled by multiple biotic and abiotic factors, and it is essential to compare lakes at different environmental settings to have a fuller understanding of lacustrine ichnology. Herein, we report on a trace assemblage comprising both invertebrate and vertebrate tracemakers in a natural lake situated within Canadian Aspen Parkland. Using detailed observations and photogrammetry, traces made by invertebrates such as fly larvae, beetles, and slugs, and (vertebrate) shorebirds are documented. Comparisons with current ichnofacies models show that these temperate latitude trace assemblages do not fully conform to the archetypal Mermia or Scoyenia Ichnofacies. For instance, fieldwork reveals a predominance of diminutive, penetrative burrows and simple surface trails that differ from the archetypal lacustrine ichnofacies. The study highlights the impact of environmental factors, such as water saturation and seasonal changes, on trace formation and preservation, providing insights into the ichnological characteristics of high-latitude lakes. These findings contribute to palaeoenvironmental interpretations and underscore the need for further research on the ichnology of forested lake systems, especially across different seasons and geographical settings.